2017
DOI: 10.1177/0003489417731578
|View full text |Cite
|
Sign up to set email alerts
|

External Auditory Canal Foreign Body Extraction Outcomes

Abstract: Patients commonly present to the ED for removal of EAC foreign bodies. Referral to an otolaryngologist is recommended if the object is spherical or after one unsuccessful attempt at removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Foreign bodies in the EAC are very common and sufferers tend to visit hospital promptly because the effects are really annoying and sometimes painful. 10,11 A previous study showed that 85.9% of all aural FBs occurred in children, and the majority of the latter were aged 5 to 9 years. 7 The authors suggested that EAC FBs are more frequent in younger children because they are curious and careless.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies in the EAC are very common and sufferers tend to visit hospital promptly because the effects are really annoying and sometimes painful. 10,11 A previous study showed that 85.9% of all aural FBs occurred in children, and the majority of the latter were aged 5 to 9 years. 7 The authors suggested that EAC FBs are more frequent in younger children because they are curious and careless.…”
Section: Discussionmentioning
confidence: 99%
“…ENTs have determined that ED/UC success rates have ranged widely, from 12% to 86%. 7,9,11,13,14,16 Studies conducted by ED/UC personnel, however, have exhibited consistence for higher rates of success, at 78% to 88%. 1,8,[10][11][12] Although not all research conducted by ENTs has disagreed with the findings by ED/UC personnel, our rate of 17.74% success by the ED/UCs again highlights a divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the variation in findings, the literature has persistently demonstrated higher rates of aural FB removal success by associated ENT departments as compared with ED/UC departments. [8][9][10][11][12][13][14]16 Furthermore, Mingo et al 11 showed a statistically significant difference in the first-attempt success rates of ENTs (95.4%) when compared with PCPs (75%). Failure to remove aural FBs is particularly impactful for pediatric patients; each new attempt at FB retrieval may induce greater stress to the child, especially if the child experiences pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Specifically, jewelry bead FBs in the ears of children have the lowest rates of successful removal. 10,11 Because jewelry represents the majority of FBs presenting in the age group from birth to 4 years old, educational efforts and prevention strategies should target these populations (Figure 5; Table 1). Complications of ear piercings should be discussed during the newborn discharge examination and pediatric wellness visits.…”
Section: Pediatric Presentationsmentioning
confidence: 99%